TCAD simulation of thermally evaporated germanium. Issue 1 (9th December 2013) - De Iacovo, A.; Sorianello, V.; Colace, L.; Assanto, G.; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract Epitaxial growth of germanium on silicon produces large misfit and threading dislocation densities which dramatically affect electronic properties of Ge. For this reason, TCAD standard models and parameters, optimized for bulk Ge, fail when applied to Ge epilayers. In this work we describe a novel approach for the simulation of highly defected germanium films grown by thermal evaporation. We also take into account the gradient of defect concentration depending on the germanium thickness. The proposed model is successfully employed for TCAD simulations of Ge‐on‐Si pn heterojunction photodiodes, demonstrating good agreement with experimental data. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)